2014
DOI: 10.1177/0956797613516471
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Arithmetic Development

Abstract: In this article, we present the results of an 11-month longitudinal study (beginning when children were 6 years old) focusing on measures of the approximate number sense (ANS) and knowledge of the Arabic numeral system as possible influences on the development of arithmetic skills. Multiple measures of symbolic and nonsymbolic magnitude judgment were shown to define a unitary factor that appears to index the efficiency of an ANS system, which is a strong longitudinal correlate of arithmetic skills. However, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
90
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(112 citation statements)
references
References 28 publications
15
90
0
7
Order By: Relevance
“…With the exception of a small subset of our analyses (ANS acuity in Year 0 and Linear r 2 in Years 2 and 3), we found little evidence that our ANS and estimation measures uniquely predicted math outcomes when controlling for other cognitive abilities. This finding supports the conclusion that the relation between ANS acuity and symbolic math performance is often weakest in the early elementary school years (Fazio et al, 2014), and with work showing that this relationship may be mediated by other, non-ANS-related, factors (e.g., Gilmore et al, 2013;Göbel et al, 2014;Holloway & Ansari, 2009). …”
Section: Discussionsupporting
confidence: 86%
“…With the exception of a small subset of our analyses (ANS acuity in Year 0 and Linear r 2 in Years 2 and 3), we found little evidence that our ANS and estimation measures uniquely predicted math outcomes when controlling for other cognitive abilities. This finding supports the conclusion that the relation between ANS acuity and symbolic math performance is often weakest in the early elementary school years (Fazio et al, 2014), and with work showing that this relationship may be mediated by other, non-ANS-related, factors (e.g., Gilmore et al, 2013;Göbel et al, 2014;Holloway & Ansari, 2009). …”
Section: Discussionsupporting
confidence: 86%
“…With regard to preschool children, Mussolin, Nys, Content, and Leybaert (2014) showed that the ability to recognize, name and compare the magnitude of Arabic digits predicts individual differences in the ability to compare the magnitude of non-symbolic numbers (sets of train wagons), but not vice versa. Consistent with these results, Göbel et al (2014) found the ability to identify Arabic digits (mapping number symbols to number words) at school entry was a strong predictor of growth in arithmetic skills across the following school year.…”
supporting
confidence: 61%
“…show a zero-order correlation with symbolic tasks (e.g., symbolic arithmetic), this relation is often completely accounted for by a comparable symbolic task (e.g., numeral comparison) (for empirical results, see, e.g., Göbel et al, 2014;Lyons et al, 2014; for a recent meta-analysis and review, see, respectively, Schneider et al, 2016;Merkley & Ansari, 2016). In other words, symbolic numerical tasks tend to be more strongly related to one another than to nonsymbolic numerical tasks.…”
Section: Reconciling Current Results With Previous Workmentioning
confidence: 99%